Evaluating Hematological Inflammatory Markers as Predictors of Preeclampsia - Serife Ozlem Genc; Huseyin Erdal (IMR Press, 2024)
Background: Preeclampsia, affecting 2-8% of pregnancies, is characterized by new-onset hypertension, proteinuria, and edema, stemming from placental dysfunction and subsequent inflammatory cascade activation. This study aimed to test the predictive ability of hematological indices in predicting preeclampsia. Therefore, predicting the diagnosis of preeclampsia earlier with higher accuracy could potentially preserve the lives of both the mother and the fetus, while also reducing the rates of complications. Methods: This retrospective study included two groups: patients with preeclampsia and a matched control group without additional medical conditions, both having undergone childbirth in the same gestational week. The primary difference between the groups was the preeclampsia diagnosis. Hematological parameters and inflammatory indices were compared for analysis. Results: Statistical significance was observed between derived neutrophil-lymphocyte ratio (dNLR), systemic immune-inflammation index (SIRI) and pan-immune inflammation value (PIV) between groups. The dNLR and PIV showed predictive relevance for preeclampsia (p < 0.05). However, their predictive performance was weak (under the curve (AUC) <0.5). A composite index (CoI) combining these indices achieved a higher AUC of 0.62, indicating limited better predictive performance capability. Conclusions: These findings affirm the correlation between preeclampsia and increased inflammation. Inflammatory markers like the dNLR, SIRI, and PIV showed statistical significance but were not practically useful in clinical settings due to their low sensitivity and specificity. The results highlight the necessity of exploring a CoI, which combines these markers, to enhance predictive accuracy and clinical utility.